2018
DOI: 10.3390/jpm8030022
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin: The End or the End of One Size Fits All Therapy?

Abstract: Oral anticoagulants are required for both treatment and prophylaxis in many different diseases. Clinicians and patients now have a choice of oral anticoagulants, including the vitamin K antagonists (of which warfarin is the most widely used and is used as the exemplar in this paper), and direct oral anticoagulants (DOACs: dabigatran, apixaban, rivaroxaban, and edoxaban). This paper explores the recent advances and controversies in oral anticoagulation. While some commentators may favour a complete switchover t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 55 publications
0
29
0
1
Order By: Relevance
“…To date, more than 60 variant alleles in CYP2C9 have been described and the most common allele of CYP2C9 is ⁎ 1, usually considered as the wild-type genotype. CYP2C9 ⁎ 2 and CYP2C9 ⁎ 3 have been examined with respect to warfarin dosing ( Flora et al., 2017 ; Johnson et al., 2017 ; Pirmohamed, 2018 ) and it is found that patients who have one or two copies of CYP2C9 * 2 or * 3 require lower warfarin dose to achieve anticoagulation effect than those with CYP2C9 * 1 homozygous and have a greater risk of bleeding during therapy ( Johnson et al., 2011 ; Takeuchi et al., 2016 ; Cullell et al., 2018 ). Furthermore, warfarin is a specific inhibitor of the vitamin K epoxide reductase, encoded by the vitamin K epoxide reductase complex subunit 1 ( VKORC1 ) gene.…”
Section: Introductionmentioning
confidence: 99%
“…To date, more than 60 variant alleles in CYP2C9 have been described and the most common allele of CYP2C9 is ⁎ 1, usually considered as the wild-type genotype. CYP2C9 ⁎ 2 and CYP2C9 ⁎ 3 have been examined with respect to warfarin dosing ( Flora et al., 2017 ; Johnson et al., 2017 ; Pirmohamed, 2018 ) and it is found that patients who have one or two copies of CYP2C9 * 2 or * 3 require lower warfarin dose to achieve anticoagulation effect than those with CYP2C9 * 1 homozygous and have a greater risk of bleeding during therapy ( Johnson et al., 2011 ; Takeuchi et al., 2016 ; Cullell et al., 2018 ). Furthermore, warfarin is a specific inhibitor of the vitamin K epoxide reductase, encoded by the vitamin K epoxide reductase complex subunit 1 ( VKORC1 ) gene.…”
Section: Introductionmentioning
confidence: 99%
“…However, their current high price restricts access to them in many healthcare systems, and concerns over long term adherence [ 152 ], as well as patient choice, mean they are not suitable for all patients. Interestingly, bleeding risk appears equivalent between DOACs and warfarin in patients who have no VKORC1 / CYP2C9 warfarin risk alleles [ 153 ] or their anticoagulation centre-based TTR is ≥ 66% [ 154 ], and thus anticoagulant stratification based on VKORC1 / CYP2C9 genotypes has been posited [ 155 ]. Moreover, no DOAC is indicated following mechanical heart valve surgery or in those with a creatinine clearance < 15mL/min; thus, further research into the utility of warfarin PGx in these specific settings is warranted.…”
Section: Warfarinmentioning
confidence: 99%
“…Warfarin, a coumarin anticoagulant and one of the most widely used drugs in clinical medicine, is used to prevent or reduce the risks of thromboembolism. Its daily dose for satisfactory anticoagulation displays wide inter‐individual variability, ranging from 0.5 to 20 mg daily . The intensity of anticoagulation by warfarin, determined by a number of genetic and non‐genetic factors which include age and dietary and environmental factors, is measured by the international normalised ratio (INR).…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…The roles of CYP2C9 and VKORC1 polymorphisms have now been studied sufficiently exhaustively and further studies focussing on them will likely provide more of the same. While it is certainly premature to write an obituary for warfarin, now may well be an appropriate time to reconsider the justification of allocating further scarce resources to the study of its pharmacogenetics.…”
Section: What Is New and Conclusionmentioning
confidence: 99%